Analysis of Education Infrastructure during the Covid-19 Pandemic in High School Indonesian Islamic University - Qhoimah, Nurul; Fitriyana; Apridayanti, Rahayu (Proceeding International Conference on Religion, Science and Education, 2022)
The author’s purpose in making this article is to review online learning methods, especially in learning infrastructure at the Indonesian Islamic University Yogyakarta Senior High School. The result of this research is the implementation of learning in the Senior High School of the Islamic University of Indonesia using information technology. The information system used by the Indonesian Islamic University Senior High School is e-learning. Online learning activities cannot be separated from electronic devices and internet networks so that in their implementation there are obstacles such as the availability of inadequate infrastructure, namely: 1) Unstable internet connection, 2) Large quota requirements.